Real-life experience with inotersen at CEPARM, Hospital Universitário Clementino Fraga Filho, Universidade Federal do Rio de Janeiro - Moises Dias; Luiz Felipe Pinto; Marcus Vinícius Pinto; Renata Gervais; Paula Accioli; Gabriela Amorim; Mariana Guedes; Carlos Perez Gomes; Roberto Coury Pedrosa; Márcia Waddington-Cruz (Arquivos de Neuro-Psiquiatria)
Background Hereditary transthyretin amyloidosis (ATTRv) is an inherited, progressive, and fatal disease still largely underdiagnosed. Mutations in the transthyretin (TTR) gene cause the TTR protein to destabilize, misfold, aggregate, and deposit in body tissues, which makes ATTRv a disease with heterogeneous clinical phenotype.